Comparison of Prophylactic Gabapentin, Dexamethasone, and Ondansetron in Terms of Incidence of Postoperative Nausea and Vomiting in Patients Undergoing Tonsillectomy Under General Anesthesia - Zamurd, .; Afzal, Farrukh; Hassan, Anam; Hasnat, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Postoperative nausea and vomiting (PONV) is a common complication following tonsillectomy under general anaesthesia, leading to delayed recovery, prolonged hospital stays, and increased healthcare costs. Objective: This study aimed to compare the efficacy of gabapentin, dexamethasone, and ondansetron in preventing PONV in patients undergoing tonsillectomy. Methods: A randomised controlled trial was conducted at Mayo Hospital Lahore, involving 210 patients aged 12–40 years, with ASA status I–II, scheduled for tonsillectomy under general anaesthesia. Patients were randomly assigned to one of three groups: Group G (gabapentin 300 mg orally 1 hour before surgery), Group D (dexamethasone 8 mg IV at induction), and Group O (ondansetron 4 mg IV at induction). PONV was assessed using the PONV scoring system at 0 hours, 30 minutes, and 2 hours after extubation. Rescue antiemetics (metoclopramide 0.2 mg/kg IV) were administered if the PONV score was 2 or more. Results: The incidence of PONV was significantly lower in Group O (12.9%) compared to Group D (22.9%) and Group G (32.9%) (P = 0.01). Stratified analyses revealed that female gender, younger age (≤ 26 years), lower weight (<60 kg), and ASA status 1 were associated with higher PONV incidence. No significant difference was observed in PONV incidence concerning surgery duration (P > 0.05). Conclusion: Ondansetron had the lowest incidence of PONV compared to dexamethasone and gabapentin in patients undergoing tonsillectomy under general anaesthesia. Stratified data suggest that patients with female gender, younger age, and lower weight may benefit from more aggressive PONV prophylaxis.